Near‐Eye Display and Tracking Technologies for Virtual and Augmented Reality - Koulieris, G. A.; Akşit, K.; Stengel, M.; Mantiuk, R. K.; Mania, K.; Richardt, C. (Computer graphics forum, 2019)
Virtual and augmented reality (VR/AR) are expected to revolutionise entertainment, healthcare, communication and the manufacturing industries among many others. Near‐eye displays are an enabling vessel for VR/AR applications, which have to tackle many challenges related to ergonomics, comfort, visual quality and natural interaction. These challenges are related to the core elements of these near‐eye display hardware and tracking technologies. In this state‐of‐the‐art report, we investigate the background theory of perception and vision as well as the latest advancements in display engineering and tracking technologies. We begin our discussion by describing the basics of light and image formation. Later, we recount principles of visual perception by relating to the human visual system. We provide two structured overviews on state‐of‐the‐art near‐eye display and tracking technologies involved in such near‐eye displays. We conclude by outlining unresolved research questions to inspire the next generation of researchers.